FARMERS' ADOPTION LEVEL OF CORN CULTIVATION TECHNOLOGY (Zea Mays L) IN THE SUB-DISTRICT OF LABUHANBATU DISTRICT ON THE INFLUENCE OF SOCIO-ECONOMIC ASPECTS - Ida Zulfida (Pusat Publikasi Jurnal Universitas Islam Kalimantan, 2023)
Farmers are the people who use land (nature), labor, and capital to organize production in the agricultural field, whether for profit or not. Farming is a production organization.Corn (Zea mays L.) is one of the main commodities of legumes. It is a staple food in the United States because it is a good source of vegetable protein that helps diversify the food supply and ensures the nation's food security.Farmers are influenced by a variety of factors, including economic ones, such as capital control, the expectation of greater profits from farming, which will be chosen in comparison to other forms of farming. This is especially true when it comes to prioritizing optimal production results.The study was conducted in Sidorukun Village, Pangkatan District, Labuhanbatu Regency, with the goals of determining the level of farmer adoption of corn cultivation technology and the socioeconomic influence of farmers on corn cultivation technology.By using survey techniques, this study employs either quantitative or descriptive methods.According to the study's findings, the adoption rate of maize cultivation in Sidorukun village, Pangkatan District, Labuhanbatu Regency, is influenced by age, education level, duration of farming, and frequency of counseling. Additionally, corn cultivation did not adhere to all components of cultivation technology recommended by Field Agricultural Extension (PPL).